2014
DOI: 10.2527/jas.2013-6857
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral meloxicam on circulating physiological biomarkers of stress and inflammation in beef steers after long-distance transportation1

Abstract: Transportation stress can result in significant economic losses to producers due to decreased animal productivity and increased medication costs associated with sickness such as bovine respiratory disease (BRD). Meloxicam (MEL) provides pain relief and anti-inflammatory effects in cattle for several days after a single oral treatment. Our hypothesis was that MEL administration before shipping would reduce the impact of long-distance transportation on circulating physiological biomarkers of stress and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 46 publications
5
40
5
1
Order By: Relevance
“…Stress induced induction of serum Hp still involves release of production of cytokines and hepatic expression of Hp and other APP. [53] A recent study demonstrated the appearance of Hp-MMP 9 in serum after transportation suggesting transportation stress is also associated with measurable responses of neutrophils [52,54]. These studies support the further evaluation of Hp-MMP 9 complex as a marker of early inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…Stress induced induction of serum Hp still involves release of production of cytokines and hepatic expression of Hp and other APP. [53] A recent study demonstrated the appearance of Hp-MMP 9 in serum after transportation suggesting transportation stress is also associated with measurable responses of neutrophils [52,54]. These studies support the further evaluation of Hp-MMP 9 complex as a marker of early inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…Substance P (SP) concentrations were analyzed as described by Van Engen et al (2014) using nonextracted plasma collected in EDTA at 0. 5, 0.75, 1, 2, 4, 6, 8, 10, 12, 24, 48, 72, and 96 h (-10 min) after dehorning.…”
Section: Substance Pmentioning
confidence: 99%
“…Substance P (SP) concentrations were analyzed as described by Van Engen et al (2014) using nonextracted plasma. Samples were assayed in duplicate with the reported concentration equaling the average SP concentration between duplicates.…”
Section: Substance Pmentioning
confidence: 99%
“…Dehorning or disbudding cattle is a management procedure commonly performed on nearly 95% of US dairy operations (USDA, 2010). Horns or horn buds are primarily removed to accommodate production practices and prevent economic loss due to carcass bruising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation